Income Comparison Before And After The Application Of CBIB In The Sawah Villages Kampar District Northen Kampar Regency Riau Province - Elvi Syahrin Situmeang; Eni Yulinda; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on 21th until 31th May 2013. This study aims to explain of thechanges in cultivication techniques before and after applying CBIB and calculate how much thechange in income of farmers. The method used in this study is a survey method with five repondentcultivication apply CBIB and pass the certification.The results of this study detected cultivication Leptobarbus hoevenli fish that pass thecertification of CBIB, Leptobarbus hoevenli fish of familiar name is kelemak fish. There werechanges in cultivication techniques cleanliness of facilities and equipment, water management,feeding, harvesting, handling result, transport, waste disposal, record keeping and corrective action.An increase in the income of fish farmers with an average percentage of 8,53% or Rp. 1.322.000.Key words : CBIB, Leptobarbus hoevenli, Sawah Villages